Hubungan Agama dan Negara dalam Islam - Astika, Hani (Al-Manahij: Jurnal Kajian Hukum Islam, 2008)
State and religion relationship is a phenomenon which generating continuous approaches among experts. This is because of variant interpretation toward religion as a part of a state or vice versa.